Artificial Intelligence–Based Human Resource Management and Employee Performance: The Mediating Role of Digital Skills and the Moderating Effect of Technology Acceptance in Indonesian Manufacturing Firms - Kusworo, Ahmad Dzulfikri Budi (IJBLE Scientific Publications Community Inc., 2026)
This study examines the effect of artificial intelligence–based human resource management (AI-based HRM) on employee performance with digital skills as a mediating variable and technology acceptance as a moderating variable. The research adopts a quantitative explanatory approach using a cross-sectional survey design. Data were collected from 300 permanent employees of manufacturing firms in Indonesia and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that AI-based HRM has a significant positive effect on employee performance. Digital skills partially mediate the relationship between AI-based HRM and employee performance, while technology acceptance positively moderates the effect of AI-based HRM on digital skills. This study contributes to the AI–HRM literature by integrating the Resource-Based View and the Technology Acceptance Model and offers practical insights for manufacturing firms seeking to align AI adoption with employee digital capability development.